2012
DOI: 10.1175/mwr-d-11-00315.1
|View full text |Cite
|
Sign up to set email alerts
|

Orographic Effects and Evaporative Cooling along a Subtropical Cold Front: The Case of the Spectacular Saharan Dust Outbreak of March 2004

Abstract: On 2 March 2004 a marked upper-level trough and an associated surface cold front penetrated into the Sahara. High winds along and behind this frontal system led to an extraordinary, large-scale, and long-lived dust outbreak, accompanied by significant precipitation over parts of Algeria, Tunisia, and Libya.This paper uses sensitivity simulations with the limited-area model developed by the Consortium for SmallScale Modeling (COSMO) together with analysis data and surface observations to test several hypotheses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 50 publications
0
8
1
Order By: Relevance
“…While previous work had identified a hydraulic jump as a signal of downslope wind storm genesis in a case study of northwest Africa (Gläser, Knippertz, & Heinold, ), we show here that such events are also found in other, quite different locations when similar synoptic‐scale flows interact with mountain ranges. We find evidence for a simulated hydraulic jump in the Bodélé Depression, where substantial dust emission has been attributed to the formation of nocturnal low‐level jets, downslope winds, and gap winds (e.g., Fiedler et al, ; Schepanski et al, ; Washington & Todd, ) and on the Arabian Peninsula in an event that occurred outside of the dominant dust storm season and has not been analyzed in depth before.…”
Section: Discussioncontrasting
confidence: 53%
“…While previous work had identified a hydraulic jump as a signal of downslope wind storm genesis in a case study of northwest Africa (Gläser, Knippertz, & Heinold, ), we show here that such events are also found in other, quite different locations when similar synoptic‐scale flows interact with mountain ranges. We find evidence for a simulated hydraulic jump in the Bodélé Depression, where substantial dust emission has been attributed to the formation of nocturnal low‐level jets, downslope winds, and gap winds (e.g., Fiedler et al, ; Schepanski et al, ; Washington & Todd, ) and on the Arabian Peninsula in an event that occurred outside of the dominant dust storm season and has not been analyzed in depth before.…”
Section: Discussioncontrasting
confidence: 53%
“…Among these, 21–22 May was characterized by northerly-northeasterly winds in Sicily, brought by a Mediterranean cyclone marking the end of an 18-day long drought. Dry surface conditions with approaching thunderstorms were ideal for gust fronts and evaporative cooling, a well-known pattern for deflation [ 42 ]. According to WMO synop reports from the hilltop meteorological station of Enna (20 km to the northeast and 350 m above Caltanissetta) on the night of 21–22 May 2011, repeated thunderstorms with or without precipitation occurred, although yielding a total precipitation of only 3 mm/12 h. This confirms the potential for evaporative cooling and the formation of gust fronts.…”
Section: Resultsmentioning
confidence: 99%
“…In order to evaluate and possibly improve the key processes for dust‐emitting winds from HSs in CMIP6 models, the storm dynamic of HSs needs to be better understood. Flow interaction with the Atlas Mountains helped in generating dust‐emitting winds during the HS in March 2004, but several open questions remain [ Gläser et al , ]. Unbalanced processes probably play an important role in the development of HSs [e.g., Kaplan et al , ] and will be further analyzed in an accompanying study.…”
Section: Discussionmentioning
confidence: 99%
“…Closer to the surface, HSs take the form of a trailing front typically to the west of an eastward moving cyclone (Figure a). An impressive HS occurred between 1 and 6 March 2004 [ Knippertz and Fink , ; Li et al , ; Min et al , ; Shao et al , ; Mangold et al , ; Gläser et al , ], shown in Figure b. The equatorward advection of the extratropical air rapidly increases the near‐surface pressure, which causes strong postfrontal near‐surface winds.…”
Section: Introductionmentioning
confidence: 99%